2018
DOI: 10.5217/ir.2018.16.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based consensus on opportunistic infections in inflammatory bowel disease (republication)

Abstract: Inflammatory bowel disease (IBD) patients are a high-risk population for opportunistic infections. The IBD group of the Chinese Society of Gastroenterology of the Chinese Medical Association organized an expert group to discuss and develop this consensus opinion. This consensus opinion referenced clinical study results from China and other countries to provide guidance for clinical practices. Eight major topics, including cytomegalovirus infection, Epstein-Barr virus infection, viral hepatitis, bacterial infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…The effective suppression of the protozoa by the antibiotic gavage and L-fucose supplementation promoted recovery in the mice. Current approaches being used for IBD treatment often do not consider the variety of the microorganisms inhabiting the gastrointestinal tract [ 85 , 86 ], including protozoa. Our results imply that this may result in health deterioration in individuals defective in gut barrier due to overgrowth of non-bacterial agents.…”
Section: Discussionmentioning
confidence: 99%
“…The effective suppression of the protozoa by the antibiotic gavage and L-fucose supplementation promoted recovery in the mice. Current approaches being used for IBD treatment often do not consider the variety of the microorganisms inhabiting the gastrointestinal tract [ 85 , 86 ], including protozoa. Our results imply that this may result in health deterioration in individuals defective in gut barrier due to overgrowth of non-bacterial agents.…”
Section: Discussionmentioning
confidence: 99%
“…Although these drugs have been shown to be highly effective in the induction and maintenance of clinical and endoscopic remission, potential AEs can cause significant morbidity and mortality. Anti-TNFs have been associated with a wide range of AEs, including the increased risk of infections (viral, bacterial, fungal, or opportunistic) [ 16 , 17 , 18 ]; hematological disorders (leukopenia, thrombocytopenia, and/or anemia as well as non-Hodgkin’s lymphoma) [ 19 , 20 , 21 , 22 , 23 ]; and dermatological AEs including skin malignancies, psoriasis, granuloma annulare, interstitial granulomatous dermatitis, and erythema nodosum [ 24 , 25 ]. Demyelination has been recognized as a neurological AE of anti-TNFs both in the central and peripheral nervous system [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD), which is a general term for Crohn’s disease and ulcerative colitis, is caused by opportunistic infection or immune cell infiltration. 151,152 A meta-analysis published by Radel et al . has indicated that DPP-4 inhibition can increase the risk of Crohn’s disease.…”
Section: Methods For Screening Novel Dpp-4 Inhibitorsmentioning
confidence: 99%